Fighting the stigma surrounding mental health - Zakaria, Rozanizam (Revon Media Sdn Bhd, 2023)
World Mental Health Day on Oct 10th suits this issue very well. The Ministry of Health (MoH) chose the theme Mental Health for All and Fight Against Stigma for the celebration. World Mental Health Day aims to reduce the stigma surrounding mental health problems and encourage people to seek help and support for their mental health concerns. The stigma and misinformation that frequently surround mental health concerns must be reduced, and increasing awareness and understanding of mental health is essential to motivating people to seek treatment when they need it.